ANALISA PENGARUH PENGGUNAAN CATALYTIC CONVERTER PADA MESIN MOTOR EMPAT LANGKAH TERHADAP PENURUNAN EMISI GAS BUANG - ., Zulfah; Wibowo, Agus; Hartoni, Untung (ENGINEERING, 2011)
Using the motorcycle which is more, it is influenced the pollution from the exhaust pipe in  the air. The contains of Carbonmonocsida (CO), Oksida Nitrogen (NOx), Hydrocarbon (HC) and the other things which are accumulated and will be influenced the human’s healthy and finally it is caused die.The collecting data is taken directly by researcher from the laboratory and also from the source from the person in  which  is called an interview and it had been documented in well, the documentation is connecting wich the gas and pollution. The development of Catalytic Converter had been reducing the pollution, but it is not maximize. Adding the plat of cooper in Catalytic Converter will be an alternative to reduce the pollution on it. From the research the writer get the data before using the Catalytic Converter the four stroke exhaust pipe produced 2,238 %  CO volume, HC 222,8 ppm volume. The second research on the standard exhaust pipe produced 1,66 % CO and HC 131 ppm volume. The research which is given the cooper Catalytic Converter produced only 1,66 % CO and HC 71,4 ppm volume. From the data the writer  can conclude that cooper Catalytic Converter able to reduce the pollution from the motorcycle.Keywords: Pollution, Catalytic Converter, Cooper.